2022
DOI: 10.1093/cercor/bhac278
|View full text |Cite
|
Sign up to set email alerts
|

Selective corticofugal modulation on sound processing in auditory thalamus of awake marmosets

Abstract: Cortical feedback has long been considered crucial for the modulation of sensory perception and recognition. However, previous studies have shown varying modulatory effects of the primary auditory cortex (A1) on the auditory response of subcortical neurons, which complicate interpretations regarding the function of A1 in sound perception and recognition. This has been further complicated by studies conducted under different brain states. In the current study, we used cryo-inactivation in A1 to examine the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Exploring the auditory brain in terms of listening loops conditioned for effective sensing and communication with the outside world is, in fact, how the research field is starting to align ( Bajo et al, 2010 ; Robinson et al, 2016 ; Weible et al, 2020 ; Yudintsev et al, 2021 ; Wang et al, 2022 ), powered by a combination of new technologies applied generally across sensory neuroscience (e.g. Zingg et al, 2017 ; Williamson and Polley, 2019 ), and a specific re-imagining of the structure and function of subcortical auditory structures ( Xiong et al, 2015 ; Bidelman et al, 2018 ; Lohse et al, 2021 ).…”
Section: Listening Loops and The Adapting Brainmentioning
confidence: 99%
“…Exploring the auditory brain in terms of listening loops conditioned for effective sensing and communication with the outside world is, in fact, how the research field is starting to align ( Bajo et al, 2010 ; Robinson et al, 2016 ; Weible et al, 2020 ; Yudintsev et al, 2021 ; Wang et al, 2022 ), powered by a combination of new technologies applied generally across sensory neuroscience (e.g. Zingg et al, 2017 ; Williamson and Polley, 2019 ), and a specific re-imagining of the structure and function of subcortical auditory structures ( Xiong et al, 2015 ; Bidelman et al, 2018 ; Lohse et al, 2021 ).…”
Section: Listening Loops and The Adapting Brainmentioning
confidence: 99%
“…The inferior colliculus (IC) is an evolutionarily conserved midbrain structure that plays a pivotal role in AM perception (Champoux et al, 2007), and the first major central auditory structure where neuronal responses to AM sounds change from a temporal-to a rate-based representation (Hewitt and Meddis, 1994;Lorenzi et al, 1995;Krishna and Semple, 2000;Nelson and Carney, 2007;Tan and Borst, 2007;Ter-Mikaelian et al, 2007;Dicke et al, 2007;Geis and Borst, 2009;Wang et al, 2022). Indeed, although neurons in sub-tectal brainstem nuclei phase-lock their firing rates to AM fluctuations, mean spike rates are often insensitive to the temporal characteristics of the sound envelope (Frisina et al, 1990;Rhode and Greenberg, 1994;Zhao and Liang, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, although the corticothalamic system has been much less well-understood compared with the thalamocortical system, descending presynaptic terminals greatly outnumber their ascending counterparts at least in the visual and somatosensory thalamus 11,[16][17][18] , suggesting their important contribution to thalamic function. Indeed, it has been shown that the corticothalamic pathways can dynamically modulate thalamic activity 19,[20][21][22][23][24][25] , enabling active and adaptive sensory processing in the thalamus 20,[26][27][28] . However, despite the fact that both layer 5 (L5) and layer 6 (L6) neurons project to the thalamus, most of our knowledge about the organization and function of the corticothalamic descending pathways have actually been obtained from layer 6 projections in the lemniscal sensory systems 3,20,26,29,30 , which provide feedback inputs to the primary sensory thalamic nuclei.…”
Section: Introductionmentioning
confidence: 99%